Sectoral Engines of Growth in Developing Asia: Stylized Facts and Implications - Jesus Felipe; Miguel León-Ledesma; Matteo Lanzafame; Gemma Estrada (Asian Development Bank (ADB), 2007)
This paper provides an analysis of developing Asia's growth experience from the point of view of its structural transformation during the last three decades. The most salient feature of this transformation has been the significant decrease in the share of agriculture and the parallel increase in the share of services. The analysis uses Kaldor's framework to discuss whether industry plays the role of engine of growth in developing Asia. The empirical results show first, that both industry and services play such a role; and second, there is evidence of endogenous, growth-induced technological progress. Likewise, the technology gap approach supports the view that technological spillovers have fostered growth in developing Asia.
hdl:11540/1871
Keywords: 330; Strukturwandel; Externer Effekt; Technischer Fortschritt; Spillover-Effekt; Entwicklung; Asien